How secure is the Advanced Encryption Standard with random ShiftRows against Fault Analysis - Peñate, Adrián Alfonso; Arrozarena, Pablo Freyre (Journal of Science and Technology on Information security, 2020)
Abstract— With the approve of the cryptographic algorithm Rijndael as the AES (Advanced Encryption Standard) and a collection of works exists with the purpose that one or several of its internal functions depend on the selected key. In this work we will study a fault analysis model against the algorithm AES, and then we will analyze for dynamic (in the key-dependency sense) cryptographic algorithms based on AES, in the which ones the internal function ShiftRows is randomly selected in every round, how strong is this attack. Tóm tắt— Với việc thuật toán mã hóa Rijndael được chấp nhận là Tiêu chuẩn mã hóa nâng cao (Advanced Encryption Standard - AES), và một loạt các công trình nghiên cứu về một hoặc một số chức năng bên trong của thuật toán phụ thuộc vào khóa đã được công bố. Bài báo này trình bày về nghiên cứu mô hình phân tích lỗi dựa trên thuật toán AES và phân tích các thuật toán mã hóa động (theo nghĩa phụ thuộc khóa) dựa trên AES. Trong đó, các hàm nội bộ ShiftRows được chọn ngẫu nhiên trong mỗi vòng, để đánh giá mức độ nguy hiểm của cuộc tấn công.